HUBUNGAN KEBIJAKAN KOMITE OLAHRAGA NASIONAL INDONESIA DENGAN PEMBINAAN OLAHRAGA DI KABUPATEN SEMARANG TAHUN 2021-2022 - Kusumo, Hariyo; Junaidi, Said (Indonesian Journal of Physical Education and Sport Science, 2023)
Purpose Study. The pandemic covid 19 situation could have an impact on the Indonesian National Sports Committee's policy and sports coaching. is to determine the relationship between the Indonesian National Sports Committee's policy and sports coaching of Semarang Regency in 2021-2022. Materials and Methods. This study uses a correlational descriptive method carried out in KONI Semarang Regency, Central Java Province by using a questionnaire given to athletes who are preparing for provincial sports week qualification in 2023. All policy of the national sports committee questionnaire items are valid (smallest value is 0.742) and reliable (cronbach alpha =0.79). All sports development questionnaire items are valid (smallest value is 0.78) and reliable (Cronbach alpha=0.8). The samples are 28 respondents. Sampling technique was total sample. The sample was filtering with inclusion and exclusion criteria. Inclusion criteria were actively training and superior athletes (athletics, aeorosport/paragliding, karate, taekwondo, and wushu). Results. The data analysis was used spearman rank correlation test. The relationship is very strong and positive (correlation coefficient 0.889). There is a significant relationship between the Indonesian National Sports Committee's Policy (X) and Sports Coaching (Y) in Semarang Regency. The significance of the p value was 0.00 <0.05, the level of CI was 95%. Conclusion. There is a correlation between KONI policy and sports coaching. The better Indonesian National Sports Committee's policy was influencing sports development. Suggestions for further research are focused on communication styles to motivate athlete coaching.